Solve `x -4(x - 3) = 6 - (x - 4).`

First distribute -4 on the left side of equation and distribute (-) on right side of equation.

`x - 4x + 12 + 7 = 6 - x + 4`

Now combine like terms on each side.

`-3x + 19 = -x + 10`

Add x to each side to remove x from right side.

`-3x + x + 19 = -x + x + 10`

`-2x + 19 = 10`

Subtract 19 from each side to isolate x.

`-2x + 19-19 = 10 - 19`

`-2x = -9`

Divide both sides by -2 to isolate x.

`(-2x)/(-2) = (-9)/(-2)`

`x = 9/2`

**The solution is x = `9/2` or 4.5.**

Solve multiplication and parenthesis first.

`x-4x+12+7=6-x+4`

Add x to both sides, so that all x terms are on the same side.

`x-4x+x+12+7=6+4`

Subtract 12+7 to both sides, so that all the constants are on the same side.

`x-4x+x=6+4-12-7`

Simplify each side.

`-2x=-9`

Divide both sides by -2

`x=(-9)/-2`

**Therefore x=4.5**

## See eNotes Ad-Free

Start your **48-hour free trial** to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Already a member? Log in here.